Archeologia pubblica in Italia - Molducci, Chiara; NUCCIOTTI, MICHELE; Bonacchi, Chiara (Strumenti per la didattica e la ricerca, 2019)
This volume offers a representative and updated selection of the themes and proposals presented during the first congress of Public Archaeology in Italy, held in Florence in 2012. Public Archaeology is one of the most dynamic and innovative sectors of the contemporary humanistic and social research, and it has progressively established itself internationally as a scientific and cultural movement for the positive innovation of the relationship between research on the past and 'new' social needs. The 2012 congress in Florence contributed to defining the priorities and methodologies of this sector, which nowadays is rapidly expanding in Italy and which over the last decade has earned a place in university courses, scientific journals and advanced design experiments.